Correaltion of Thrombolysis in Myocardial Infarction Risk Score and Angiographic Score in Patients with ST-Elevation in Myocardial Infarction - Mohammadreza Akhbari; Hamid Sanei; Masoume Sadeghi; Mojtaba Akbari; Nahid Sistan; Iraj Jafaripour; Mehradad Rashidi Benam; Nafishe Motamedi (مجله دانشکده پزشکی اصفهان, 2009)
Background: Myocardial Infarction is a common and lethal disease, especially in first hours. Rapid and correct decision is essential for priority of advance therapies and this study follows the accuracy of a scoring system for this triage. The aim was to assess the correlation of Thrombolysis in Myocardial Infarction Risk score and Angio score in patients with ST Elevation Myocardial Infarction. Methods: In this cross sectional study, 240 patients with ST elevation myocardial infarction from CCU of universal hospitals participated in the study. Thrombolysis in myocardial infarction risk score was calculated and during 2 month they underwent angiography and follow up. Findings: Mean age was 60.02 and 79 patients were female. Correlation between thrombolysis in myocardial infarction risk and angio score was significant (P < 0.001). Correlation between ejection fraction and thrombolysis in myocardial infarction risk score (P < 0.001) and angio score with age (P < 0.001) was significant too. There was no significant correlation between Angio score and recurrent angina (P = 0.143), rehospitalization (P = 0.524) and death (P = 0.179). Pearson's correlation showed significant relation between thrombolysis in myocardial infarction risk score and angio score (P < 0.001, r = 0.556). Conclusion: This correlation shows that thrombolysis in myocardial infarction risk score probably can be used for evaluating angiographic extent of coronary artery disease. Simple clinical use of this score at bedside if confirms with a prospective cohort study, makes this score a method to stratify patients in high and low risk groups and accordingly diagnostic– therapeutic strategies.